2018
DOI: 10.1002/smll.201802709
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Subcellular Compartment Targeting Effect of Porous Coordination Cages for Enhancing Cancer Nanotherapy

Abstract: Understanding the key factors for successful subcellular compartment targeting for cargo delivery systems is of great interest in a variety of fields such as bionanotechnology, cell biology, and nanotherapies. However, the fundamental basis for intracellular transportation with these systems has thus far rarely been discussed. As a cargo vector, porous coordination cages (PCCs) have great potential for use in cancer nanotherapy and to elucidate fundamental insight regarding subcellular compartment targeting. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 63 publications
2
42
0
Order By: Relevance
“…S1-S7 in the ESM. The cage complex PCC-1 was designed and synthesized by solvothermal method by our group [26]. It was obtained as bright yellow polyhedron shaped crystals from the N,N-dimethylformamide (DMF) solution.…”
Section: Formation Of Porous Coordination Cagementioning
confidence: 99%
See 1 more Smart Citation
“…S1-S7 in the ESM. The cage complex PCC-1 was designed and synthesized by solvothermal method by our group [26]. It was obtained as bright yellow polyhedron shaped crystals from the N,N-dimethylformamide (DMF) solution.…”
Section: Formation Of Porous Coordination Cagementioning
confidence: 99%
“…Previously, we successfully applied three kinds of PCCs for targeting designated subcellular organelles within the living cells. It was found that specific targeting delivery of anti-cancer drug will significantly improve cytotoxicity for different cell lines [26].…”
Section: Introductionmentioning
confidence: 99%
“…Host-guest chemistry is a key feature of MOCs that has been extensively studied. [21][22][23][24][25] The incorporation of chemicals within the well-enclosed cage interior promotes the stabilization, [26,27] protection, [28][29] and new reactivity of guest molecules, [21,30] these effects have found use in molecular recognition, [31][32][33] chemical sensing, [34][35][36][37] gas capture, [38][39][40][41][42][43] molecular separations, [44][45][46] drug delivery, [47][48][49][50][51] bioimaging [21,52,53] as well as the exploration of new catalysis pathways. [21,22,[54][55][56][57][58][59][60] All binding events also cause subtle structural host perturbations, with negligible effects in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Metallosupramolecular assemblies such as metal-organic nanocapsules (MONCs) and/or nanocages are potentially useful models for such complex biological processes, 4,5 and are also promising with regard to energy storage, [6][7][8][9][10] molecular encapsulation, [11][12][13][14][15] catalytic, [16][17][18] and biomedical applications. 19,20 To date, synthetic chemists have been able to isolate discrete cages consisting of more than 100 precisely designed units through metal coordination. 21 A longstanding challenge, however, is the rational combination of simple components to form hierarchical superstructures with a similar level of assembly complexity as proteins.…”
Section: Introductionmentioning
confidence: 99%